Bringing adaptive management to life: Insights from practice - and Arora, Anmol; Gogoi, Elizabeth; Joy, Divya; Kumar, Pankaj; Luthra, Rajni; Pal, Uma; Pervaiz, Arif (Oxford Policy Management, 2019)
The increasing popularity of adaptive programmes in the development sector in the past decade is partly a response to the complex and interconnected challenges facing many developing countries, including the impacts of climate change. The pathway to adapting to climate change is unknown, and there are many deep-rooted institutional, political, economic and social barriers. Adaptive programmes provide the flexibility to allow those delivering the technical assistance to support governments to experiment with different entry points and to adapt or change course when some are not successful. The Action on Climate Today (ACT) programme is a five-year adaptive programme that aims to strengthen systems of planning and delivery for adaptation to climate change in South Asia. As the programme draws to a close, this Learning Paper reflects on some of the major lessons learnt on the challenges and opportunities of using an adaptive programme management approach to support governments to adapt to climate change. The authors are members of the ACT implementation team, representing the management, operational and technical teams, from across different locations. The paper therefore reflects their first-hand account of the reality of implementing adaptive programmes. The paper sets out a framework for the essential ingredients of an adaptive programme management approach. These include a set of essential core principles: an evolving theory of change; a locally led and politically savvy delivery approach; experimentation and learning; and stakeholder alignment. It also includes two sets of essential resources required: management flexibility and adequate financial resources. The paper then provides learning from ACT on how to operationalise these core principles and mobilise the necessary resources. It gives detailed examples of challenges faced by ACT with regard to each component of the framework, and how the programme has overcome them, as well as retrospective reflections of additional actions the programme could have taken. A set of case studies unpacks how adaptive programme management has been operationalised in practice in particular locations. The authors are confident that the impact ACT has had owes in large part to it being an adaptive programme. The programme’s flexibility, decentralised structure and strong emphasis on learning have meant the team has been able to respond to opportunities as they have emerged and to invest time and resources where there was most potential for impact. However, this paper is also honest about the challenges ACT has faced as an adaptively managed programme. The paper therefore concludes with a set of lessons learnt from ACT for the benefit of others designing and delivering adaptive programmes on climate change and other issues.